Diploneis fenestrata sp. nov. (Bacillariophyta), a new aerophilic diatom species from Zambia, Africa - Taylor, Jonathan C.; Karthick, Balasubramanian; Cocquyt, Christine; Lang, Pauline (Phytotaxa, 2014)
Diploneis fenestrata, a new aerophilic diatom is described from Lumangwe falls, Zambia. This novel species occurs as an epiphyte on the roots and stems of trees located within the spray zone of the falls. Its morphology was examined with both light and scanning electron microscopy. Diploneis fenestrata is distinguished from other taxa in the genus Diploneis by its prominent square openings ranging in number from 4-14 occurring within the area of the longitudinal canal only at the outer cell wall. The occurrence of these characteristic square openings found in the genus Diploneis is further discussed.